Augmented Perception Through Spatial Scale Manipulation in Virtual Reality for Enhanced Empathy in Design-Related Tasks - Zhang, Jingjing; Dong, Ze; Bai, Xiaoliang; Lindeman, Robert W.; He, Weiping; Piumsomboon, Thammathip (Frontiers in Virtual Reality, 2022)
This research explores augmented perception by investigating the effects of spatial scale manipulation in Virtual Reality (VR) to simulate multiple levels of virtual eye height (EH) and virtual interpupillary distance (IPD) of the VR users in the design context. We have developed a multiscale VR system for design applications, which supports a dynamic scaling of the VR user's EH and IPD to simulate different perspectives of multiple user's groups such as children or persons with disabilities. We strongly believe that VR can improve the empathy of VR users toward the individual sharing or simulating the experience. We conducted a user study comprising two within-subjects designed experiments for design-related tasks with seventeen participants who took on a designer's role. In the first experiment, the participants performed hazards identification and risks assessment tasks in a virtual environment (VE) while experiencing four different end-user perspectives: a two-year-old child, an eight-year-old child, an adult, and an adult in a wheelchair. We hypothesized that experiencing different perspectives would lead to different design outcomes and found significant differences in the perceived level of risks, the number of identified hazards, and the average height of hazards found. The second experiment had the participants scale six virtual chairs to a suitable scale for different target end-user groups. The participants experienced three perspectives: a two-year-old child, an eight-year-old child, and an adult. We found that when the designer's perspective matched that of the intended end-user of the product, it yielded significantly lower variance among the designs across participants and more precise scales suitable for the end-user. We also found that the EH and IPD positively correlate with the resulting scales. The key contribution of this work is the evidence to support that spatial scale manipulation of EH and IPD could be a critical tool in the design process to improve the designer's empathy by allowing them to experience the end-user perspectives. This could influence their design, making a safer or functionally suitable design for various end-user groups with different needs.